A novel upregulated LncRNA‐AC026150.8 promotes chemo‐resistance and predicts poor prognosis in acute myeloid leukemia. (19th October 2021) - Zhang, Henan; Zhao, Yue; Liu, Xuan; Liu, Yusi; Wang, Xiaohui; Fu, Yu; Fu, Shuang; Zhang, Jihong
Abstract: Background: AML is a common hematological malignancy with poor prognosis, the pathogenesis is still unclear. lncRNA takes part in occurrence and development of AML. This research aims to explore new differentially expressed lncRNAs and their effects on AML. Methods: Database‐based bioinformatics analysis was performed to screen differentially expressed lncRNA in AML, real‐time PCR was used to analyze gene expression. Kaplan–Meier survival analysis was performed to determine prognostic effect of AC026150.8 in AML. The cell drug resistance experiment was performed to test effect of AC026150.8 on chemo‐resistance of AML cells. Catrapid online software and RNA pull‐down, mass spectrometry, western‐blot were used to predict and verify the combination of AC026150.8 and RNA splicing factors. Results: AC026150.8 was upregulated in AML patients and related to poor prognosis. High leukocyte counts, FAB classification, MLL‐AF9 expression and NPM1 mutations were associated with high AC026150.8 expression. Upregulated of AC026150.8 increased the drug resistance of AML cells. AC026150.8 could be combined with splicing factor PCBP1. Conclusions: For the first time, our study found that the upregulated AC026150.8 in AML is related to poor prognosis, overexpression of AC026150.8 could increase drug resistance of AML cells, and confirmed its scaffolding effect in combination with splicing factors. It is necessary to further study AC026150.8 and its downstream target genes to clarify the mechanism of AC026150.8 in AML. Abstract : We found a new upregulated LncRNA‐AC026150.8 in AML patients, which was related to poor prognosis. The upregulated AC026150.8 increased the drug resistance of AML cells. AC026150.8 can interact with the splicing factor PCBP1 through scaffolding, and it is speculated that AC026150.8 can regulate the drug resistance of AML cells through this effect.